Caregivers' attentional bias to pain: does it affect caregiver accuracy in detecting patient pain behaviors?. Issue 1 (January 2015) - Mohammadi, Somayyeh; Dehghani, Mohsen; Khatibi, Ali; Sanderman, Robbert; Hagedoorn, Mariët
Abstract : Abstract: Attentional bias to pain among family caregivers of patients with pain may enhance the detection of pain behaviors in patients. However, both relatively high and low levels of attentional bias may increase disagreement between patients and caregivers in reporting pain behaviors. This study aims to provide further evidence for the presence of attentional bias to pain among family caregivers, to examine the association between caregivers' attentional bias to pain and detecting pain behaviors, and test whether caregivers' attentional bias to pain is curvilinearly related to patient and caregiver disagreement in reporting pain behaviors. The sample consisted of 96 caregivers, 94 patients with chronic pain, and 42 control participants. Caregivers and controls completed a dot-probe task assessing attention to painful and happy stimuli. Both patients and caregivers completed a checklist assessing patients' pain behavior. Although caregivers did not respond faster to pain congruent than pain incongruent trials, caregiver responses were slower in pain incongruent trials compared with happy incongruent trials. Caregivers showed more bias toward pain faces than happy faces, whereas control participants showed more bias toward happy faces than pain faces. Importantly, caregivers' attentional bias to pain was significantly positively associated with reporting pain behaviors in patients above and beyond pain severity. It is reassuring that attentional bias to pain was not related to disagreement between patients and caregivers in reporting pain behaviors. In other words, attentional bias does not seem to cause overestimation of pain signals. Abstract : Caregivers with higher attention to pain report more pain behaviors. Caregivers' attention to pain was not related to caregiver–patient disagreements in reporting pain behaviors.